2019
DOI: 10.1001/jamadermatol.2018.5641
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sleep Disturbances and Exhaustion in Mothers of Children With Atopic Dermatitis

Abstract: This longitudinal cohort study analyzes data collected across 11 years to assess the association between the presence and severity of atopic dermatitis in children and maternal sleep disturbance among a population-based UK cohort of mother-child pairs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 48 publications
(94 reference statements)
2
35
0
Order By: Relevance
“…Analysis of the cohort data from 11,649 mother-child pairs who were followed up with a time-varying measure of child AD activity and severity as well as self-reported maternal sleep measures repeated at multiple time points for children aged 6 months to 11 years showed that mothers of children with AD reported difficulty falling asleep, subjectively insufficient sleep, and daytime exhaustion throughout the first 11 years of childhood. 13,14 These data suggest that sleep disturbance may be a family affair.…”
Section: Practice Pointsmentioning
confidence: 87%
See 1 more Smart Citation
“…Analysis of the cohort data from 11,649 mother-child pairs who were followed up with a time-varying measure of child AD activity and severity as well as self-reported maternal sleep measures repeated at multiple time points for children aged 6 months to 11 years showed that mothers of children with AD reported difficulty falling asleep, subjectively insufficient sleep, and daytime exhaustion throughout the first 11 years of childhood. 13,14 These data suggest that sleep disturbance may be a family affair.…”
Section: Practice Pointsmentioning
confidence: 87%
“…12 The well-being and development of children are strongly influenced by the physical and psychosocial health of parents/guardians. Two studies by Ramirez and colleagues 13,14 published in 2019 examined sleep disturbances and exhaustion in mothers of children with AD. Data for the studies came from the Avon Longitudinal Study of Parents and Children.…”
Section: Practice Pointsmentioning
confidence: 99%
“…22,32 The bedtime routine module focused on establishing and implementing a consistent bedtime routine. 6,8,9,12,18 A template was provided for participants to build their personalized bedtime routine, including activities they must do to prepare for bed (ie brush teeth, put on pajamas) and activities that help them relax (ie read, quiet music). Bedtime routine goals focused on the implementation process of the bedtime routine, ranging from trialing (and possibly revising) a new bedtime routine, increasing the number of nights the bedtime routine is used, and choosing consistent time to start the routine.…”
Section: Skip Developmentmentioning
confidence: 99%
“…Sleep quality goals included establishing a consistent bedtime and/or wake time, use of bed for sleep only, and bedtime relaxation (progressive relaxation, belly breathing). 12,19,22,23,34,35 Goals related to sleep quantity were based on the National Sleep Foundation's age-specific sleep duration recommendations. 36…”
Section: Skip Developmentmentioning
confidence: 99%
See 1 more Smart Citation